Brainstem Encephalitis With Low-Titer Acetylcholine Receptor Antibodies Mimicking Myasthenia Gravis - Ayzenberg, Ilya; Ellrichmann, Gisa; Schroeder, Christoph; Tönges, Lars; Klasing, Anja; Pappa, Vaia; Brück, Wolfgang; Gold, Ralf (Frontiers in Neurology, 2019)
Objective: To report a rare case of brainstem encephalitis with low-titer acetylcholine receptor antibodies mimicking myasthenia gravis. Methods: The patient was investigated with repeated brain MRI, CSF examination, repetitive nerve stimulation, thoracic CT and serologic screening. Our patient passed away and finally autopsy revealed a definitive diagnosis. Written informed consent was obtained from the relatives of the patient for access to clinical files for research purposes and publication. Results: We present a young woman with a subacute bulbar syndrome, who was initially diagnosed with myasthenia gravis based on clinical finding and elevated acetylcholine receptor antibodies. Episodes of numbness in the pharynx and tongue and moderate saccadic horizontal and vertical pursuits were atypical. Despite initial stabilization with intravenous immunoglobulins she developed acute asphyxia after regurgitation of food and had to be resuscitated with ultimately lethal outcome. Autopsy revealed an autoimmune T-cell mediated brainstem encephalitis. Serological screening revealed positive GAD and Ma2 autoantibodies, indicating its probable paraneoplastic nature. Conclusions: Brainstem encephalitis is an important differential diagnosis even in seropositive bulbar myasthenia gravis, as several autoimmune processes often co-occur. Sudden unexpected death must be taken into account in brainstem encephalitis, requiring prolonged monitoring of the patients.